1993
DOI: 10.1128/aac.37.7.1420
|View full text |Cite
|
Sign up to set email alerts
|

Potent inhibition of Epstein-Barr virus by phosphorothioate oligodeoxynucleotides without sequence specification

Abstract: We found that 28-mer phosphorothioate oligodeoxynucleotides (S-oligos) with and without sequence specificity complementary to Epstein-Barr virus (EBV) genes are potent inhibitors of EBV replication in cell culture. The decrease in the amount of EBV DNA, the activity of intracellular viral DNA polymerase, and virus production were dose dependent, with a 90%o inhibitory dose of approximately 0.5 ,uM. No inhibition of cell growth was observed with the S-oligos at concentrations up to 20 uM. The mechanism of actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…While L-I-OddU at 20 M has activity that is slightly better than that of DHPG at 20 M, with an anti-HHV8 activity of 60% compared to 41% (data not shown), it shows no advantage over ACV in our varicellazoster virus system, with EC 50 s of 17 M for L-I-OddU and of 4 M for ACV (data not shown). Only EBV showed significant increased selectivity, with an L-I-OddU EC 50 that was Ͼ1,000-fold lower than the EC 50 of 50 M for ACV. Our previous studies indicated that the action(s) responsible for the anti-EBV activity of L-I-OddU could be dependent on EBV-specific proteins (28).…”
Section: Epstein-barr Virus (Ebv) Is An Important Human Pathogenmentioning
confidence: 99%
See 2 more Smart Citations
“…While L-I-OddU at 20 M has activity that is slightly better than that of DHPG at 20 M, with an anti-HHV8 activity of 60% compared to 41% (data not shown), it shows no advantage over ACV in our varicellazoster virus system, with EC 50 s of 17 M for L-I-OddU and of 4 M for ACV (data not shown). Only EBV showed significant increased selectivity, with an L-I-OddU EC 50 that was Ͼ1,000-fold lower than the EC 50 of 50 M for ACV. Our previous studies indicated that the action(s) responsible for the anti-EBV activity of L-I-OddU could be dependent on EBV-specific proteins (28).…”
Section: Epstein-barr Virus (Ebv) Is An Important Human Pathogenmentioning
confidence: 99%
“…Several compounds have shown anti-EBV activity in cell culture systems, including acyclovir (ACV), ganciclovir (DHPG), 2Ј-fluoro-5-methyl-␤-D-arabinofuranosyl uracil (D-FMAU), and (S)-1-(3-hydroxy-2-phosphonyl-methoxypropyl)cytosine (cidofivir) (6,9,26,27,36,50,52). However, the clinical application of many of these compounds is restricted by severe side effects (52).…”
Section: Epstein-barr Virus (Ebv) Is An Important Human Pathogenmentioning
confidence: 99%
See 1 more Smart Citation
“…For determination of Epstein-Barr virus (EBV)-inhibitory effects, H1 cells, a subclone of human P 3 HR-1 cells, were used (12,28). H1 cells were maintained in log-phase growth for 2 days prior to the initiation of treatment.…”
mentioning
confidence: 99%
“…Various oncogenes have been targeted with antisense oligonucleotides resulting in suppression of cell growth and differentiation [6]. The antisense strategy has been successfully explored in vitro for the treatment of several viral infections, for example, Rous sarcoma virus [39], human immunodeficiency virus [40], influenza virus [16], herpes simplex virus [25], human papilloma virus [9], EpsteinBarr virus [38], and human cytomegalovirus [3].…”
Section: Block Of Gene Expression At the Posttranscriptional Levelmentioning
confidence: 99%